Reactive metabolite production is a targetable liability of glycolytic metabolism in lung cancer - Alba Luengo (Nature Portfolio, 2019)
Glycolysis is elevated in many cancers. In this study, the authors show that lactoylglutathione, a by-product of methylglyoxal produced from increased glycolysis, is elevated in lung cancer in mouse models and humans, arguing reactive metabolite production can be a liability for cancers.